Single-industry town as a separate political space: results of a socio-political study - D. Yu. Znamenskiy; E. V. Khorobrova (Вестник университета)
The article analyses the problems of socio-political development of towns and the place of sociological research in this process, demonstrating its importance and the relevance of studying public policy at the local level. As an object of research, special attention is paid to single-industry towns due to their vulnerability to various kinds of shocks that directly affect the social and political state of the urban community. In order to reveal the specifics of the socio-political development of a single-industry town as an isolated political space, the city of Sarov was chosen. A survey (questionnaire survey) of respondents in Sarov and an expert interview were used as the main research methods. Three hypotheses regarding the factors of political and social behaviour of Sarov’s residents of were put forward in the course of the study, one of which was later confirmed. The principal features of socio-political development of a single-industry town have been revealed.